NEUROLOGICAL ABNORMALITIES IN CHILDREN WITH TYPE 1 DIABETES MELLITUS - Jangir, Rakesh; SENGAR GS; TUSHAR DWIVEDI; NISHANT ASWANI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the study is to find out the prevalence of neurological abnormalities in children between 5 and 15 years with type-1 diabetes mellitus (T1DM) of at least 2 years duration and the risk factors associated with the development of neurological abnormalities. Methods: Hospital-based cross-sectional study on 150 Children of 5–15 years of age having type I diabetes of at least 2 years’ duration by simple random sampling fulfilling the inclusion criteria, at Department of Pediatric Medicine, Sardar Patel Medical College and P.B.M. Hospital Bikaner. Results: Mean age was 10.9±3.6 years, male to female ratio was 1.63:1. The prevalence of peripheral neuropathy was 42.3% when 1 abnormal attribute in at least 1 nerve was considered, it was 7.3% when 2 abnormal attributes in 2 nerves were considered, 4.6% had autonomic neuropathy and 4% had cognitive abnormalities. The peripheral neuropathy was subclinical in a substantial number of cases as up to 39.4% and 39.3% of T1DM cases having peripheral neuropathy had normal neuropathic symptom score and neuropathic disability score, respectively. Female with longer duration of diabetes, higher mean age of diagnosis, and higher mean HbA1c level were significantly more likely to develop peripheral neuropathy. Conclusion: Neurological complications begin quite early and insidiously in T1DM patients highlighting the importance of early and regular screening by nerve conduction study.